Influence of environmental factors on the evolution of Romanian public accounting - Nistor, Cristina Silvia; Deaconu, Adela; Mare, Codruta (Journal of Business Economics and Management, 2015)
Using a historiography approach on public accounting, this research add value to this knowledge providing a customization of the environmental influential factors for an emergent context, the Romanian one, in specific historical phases between 1831 and 2011. The critical-interpretative picture of an extended period of 180 years is complemented by an empirical approach, an original issue in accounting history. Empirical findings based on cluster analysis confirm the existence of six influential factor groups and the intergroup interdependency and provides a fundamental explanation for the effect of factors’ combination. The political system has an influence over the economic system, which impacts accounting development, the reporting and disclosure system required by users. The connection between legal and economic factors decided the type of accounting legal system. Socio-cultural factors affected the accounting policies and decided accountancy’s progress, closely linked to the educational factor whose strong influence impacted the accounting theory and practice. All this results are a benchmark for other emergent countries. First published online: 02 Sep 2014